What women know about breast cancer: In the case of Ethiopia - Yonas Biratu Terfa; Samuel Abdu Aliyu; Ebrahim Yimam Reta; Gugsa Nemera Germossa; Adugna Olani Akuma (Tehran University of Medical Sciences, 2020)
Background & Aim: Breast cancer is the leading cause of death among women worldwide. Good knowledge of breast cancer enhances timely screening, early detection, and treatment; however, women's knowledge about breast cancer is very low. Thus, this study assesses the level of knowledge regarding breast cancer among women of childbearing age living in Jimma town.  Methods & Materials: A community based cross-sectional study was conducted in Jimma town in 2018. Respondents were identified using multistage sampling methods. Data was collected using a standard questionnaire developed by cancer research UK and used in different languages in many parts of the world. Multiple logistic regression analyses were used to identify a variable with a significant association based on OR, with 95%CI and P-value of less than 0.05. Results: Out of 724 respondents, 686 gave their complete responses. The majority of 496 (72.3%) of the respondents were young adults with a mean age of 31, and about 307 (44.8%) of them had completed secondary school (9-12).  Only 35% of respondents knew breast cancer; more specifically, 20% had knowledge of risk factors, 45% had knowledge of signs and symptoms, and 39 % had knowledge of screening methods. Maternal age, educational level, marital status, occupation, source of information, and monthly income, and positive family history of breast cancer were significantly associated with women's breast cancer knowledge. Conclusion: Just over one-third (35%) of women are knowledgeable about breast cancer. However, women's breast cancer knowledge plays a great role in controlling before reaching an advanced stage.